Learning strategies, decision-making styles and conscious use of technologies in initial teacher education - Alessandra La Marca; Elif Gülbay; Valeria Di Martino (Firenze University Press, 2018)
The aim of this research is to develop a toolkit enabling to observe transversal skills of future teachers. The research was carried out with 236 students attending the Educational Technologies course at the Primary Education program at Palermo University, during academic year 2017/2018. The research hypothesis is that the knowledge of the initial situation of students, as much objective as possible, requires triangulation, comparison and integration of the information collected with three self-assessment tools. An Italian toolkit is now available. It allows to detect the following, at the beginning of the university course: (i) how students integrate ICT with disciplinary contents and teaching methodologies; (ii) the conscious use of learning strategies by them; and (iii) the degree of development of their decision-making capacity (deliberation and resolution). Strategie di apprendimento, stili decisionali e uso consapevole delle tecnologie nella formazione iniziale degli insegnanti L'obiettivo di questo studio è la messa a punto di un kit di strumenti capaci di rilevare le competenze trasversali di coloro che si preparano a svolgere la professione di insegnante. La ricerca è stata condotta con 236 studenti del Corso di laurea magistrale in Scienze della Formazione Primaria dell'Università degli Studi di Palermo, che frequentavano il corso di Tecnologie Didattiche per la Scuola Primaria e dell'Infanzia nell'anno accademico 2017/2018. L'ipotesi di base è che la conoscenza il più possibile obiettiva della situazione iniziale degli studenti richieda la triangolazione, il confronto e l'integrazione delle informazioni raccolte con tre strumenti autovalutativi. È ora disponibile un kit di strumenti in lingua italiana che permette di rilevare, all'inizio del percorso universitario, come gli studenti integrano le TIC con i contenuti disciplinari e con le metodologie didattiche, il loro utilizzo consapevole delle strategie di apprendimento e il grado di sviluppo della loro capacità decisionale (deliberazione e risolutezza).